Procedury karne w stosunku do żołnierzy sił zbrojnych Stanów Zjednoczonych oraz członków ich personelu cywilnego przebywających na terytorium Rzeczypospolitej Polskiej - Centkowski, Marek (Studia Prawnoustrojowe, 2019)
The subject of this work is to clarify the issues of criminal jurisdiction set forth in articles 13-15 of the Agreement between the Government of the Republic of Poland and the Government of the United States of America regarding the status of the armed forces of the United States of America on the territory of the Republic of Poland of December 11, 2009 in Warsaw. The author simultaneously conducts analysis of the provisions in article VII NATO SOFA, a supplemental agreement between the Governments of Poland and the United States. In addition, memorandum of Understanding between the Minister of Justice of the Republic of Poland and the Command of the Armed Forces of the United States of America in Europe regarding foreign criminal jurisdiction, signed on October 23, 2014 in Warsaw is discussed. The memorandum specifies the provisions of the above-mentioned two international agreements, describing, among other things, how to proceed with American soldiers and members of their civilian staff as perpetrators of prohibited acts. Furthermore, this document contains templates for letters addressed to US military authorities, and Polish judicial authorities with respect to the priority of jurisdiction, as well as arrangements related to the performance of official duties by the perpetrator at the time of committing a prohibited act. The authorities that supervise or conduct preparatory proceedings against members of the United States forces and their civilian personnel are military prosecutors of the regional or the district prosecutor’s offices. The Police, on the other hand and Military Police are law enforcement agencies carrying out procedural activities at the scene and carryingout activities commissioned by the military prosecutor.